Bruce Bronzan Campaign Retreat at Morris Cabin-Shaver Lake - Watkins, Howard::::::::: (1978)
Bruce Bronzan, Bob Quesada, David Brodie, Doug Jones, Gerre Gurland-Jones, Linda Bronzan, Chloe Bronzan, Randy Walsh, Sandy Walsh, Doug Broten Doug Jones, Gerre Gurland-Jones waving, David Brodie, steep metal roof